Potential treatment effect modifiers for manipulative therapy for children complaining of spinal pain.Secondary analyses of a randomised controlled trial - Dissing, Kristina Boe (Chiropr Man Therap, 2019)
BACKGROUND: In children, spinal pain is transitory for most, but up to 20% experience recurrent and bothersome complaints. It is generally acknowledged that interventions may be more effective for subgroups of those affected with low back pain. In this secondary analysis of data from a randomized clinical trial, we tested whether five indicators of a potential increased need for treatment might act as effect modifiers for manipulative therapy in the treatment of spinal pain in children. We hypothesized that the most severely affected children would benefit more from manipulative therapy. METHOD: This study was a secondary analysis of data from a randomised controlled trial comparing advice, exercises and soft tissue treatment with and without the addition of manipulative therapy in 238 Danish school children aged 9–15 years complaining of spinal pain. A text message system (SMS) and clinical examinations were used for data collection (February 2012 to April 2014). Five pre-specified potential effect modifiers were explored: Number of weeks with spinal pain 6 months prior to inclusion, number of weeks with co-occurring musculoskeletal pain 6 months prior to inclusion, expectations of the clinical course, pain intensity, and quality of life. Outcomes were number of recurrences of spinal pain, number of weeks with pain, length of episodes, global perceived effect, and change in pain intensity. To explore potential effect modification, various types of regression models were used depending on the type of outcome, including interaction tests. RESULTS: We found that children with long duration of spinal pain or co-occurring musculoskeletal pain prior to inclusion as well as low quality of life at baseline tended to benefit from manipulative therapy over non-manipulative therapy, whereas the opposite was seen for children reporting high intensity of pain. However, most results were statistically insignificant. CONCLUSIONS: This secondary analysis indicates that children more effected by certain baseline characteristics, but not pain intensity, have a greater chance to benefit from treatment that include manipulative therapy. However, these analyses were both secondary and underpowered, and therefore merely exploratory. The results underline the need for a careful choice of inclusion criteria in future investigations of manipulative therapy in children. TRIAL REGISTRATION: NCT01504698; results